Physical rehabilitation in the frailty syndrome among the elderly - Ferreira, Milene Silva; Sonoda, Lilian Tiemi; Barbosa, Sandra Alves; Franco, Fabio Gazelato de Mello; Carvalho, José Antônio Maluf de (Acta Fisiátrica, 2014)
Frail elderly are those who have intrinsic vulnerability to develop disabilities and adverse events related to health. The prevalence of frailty increases with age. The American Medical Association estimates that 40% of those over 80 years old are fragile. Objective: To demonstrate the results obtained with the rehabilitation protocol for the frailty syndrome at Vila Mariana Geriatric Outpatient Unit of the Israelita Albert Einstein Hospital. Method: Series of cases study, descriptive and retrospective of 12 elderly who have accomplish the physical rehabilitation program at Vila Mariana geriatric outpatient unit in the Israelita Albert Einstein Hospital. Results: The average age was 77 years, 75% of the participants were female with an average of 7,5 diagnoses. There was improvement in all areas evaluated: balance (p = 0.02), gait speed (p < 0.01), lower limb strength (p < 0.01) and grip strength (p < 0.01). Those who aged 80 or more showed improvement of 83% while those with less than 80 years old, showed an improvement of 41%. It was found that 8 of 10 seniors who met on the track at high risk for disability, hospitalization and death (SPPB equal or less than 9) was able to leave the risk range. It was showed improvement in at least one domain. No deterioration or complication was observed. Conclusion: The rehabilitation protocol for the frailty syndrome that was used at Vila Mariana geriatric outpatient unit was able to improve the balance, gait speed, lower limb strength and grip strength in the population studied.